1971
DOI: 10.1136/bmj.2.5758.362
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Surveys in Areas with Different Water Supplies

Abstract: SummaryCardiovascular surveys were conducted in areas with different water supplies. In two areas with hard water 243 men were seen and in three areas with soft water 357 men were seen. There was no evidence of an important difference between the two areas in blood pressure, serum cholesterol, blood sugar, or packed cell volume. A variety of measurements were made on an E.C.G. The P-R interval was significantly longer in the men in the hard water area, and a 40-complex trace showed ventricular extrasystoles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
1

Year Published

1971
1971
1985
1985

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…Various studies linked water softness to ischemic heart disease (2), to hypertension (3), to atherosclerosis (4), and to stroke (4). However, other studies do not confirm these observations (5,6).…”
contrasting
confidence: 46%
“…Various studies linked water softness to ischemic heart disease (2), to hypertension (3), to atherosclerosis (4), and to stroke (4). However, other studies do not confirm these observations (5,6).…”
contrasting
confidence: 46%
“…Depending on the geographic region and the presence or absence of soft water (the latter usually being associated with areas of increased prevalence of cardiovascular disease), different metals would become dissolved in the drinking water (Schroeder and Kraemer, 1974). There have been conflicting reports regarding the possibility of increased risk factors for CAHD disease in populations drinking soft water (Elwood et al, 1971;Stitt et al, 1973). If there were differences in known risk factors, such as blood pressure or plasma cholesterol, it is not clear whether these are secondary to the difference in the hardness of the drinking water or a cause of the difference in the observed CAHD mortality.…”
Section: Metals and Trace Elementsmentioning
confidence: 99%
“…This association may arise because of an effect of water on a known 'risk factor' such as blood pressure, or the susceptibility of the myocardium could be affected, or some process relevant to intravascular thrombosis could be involved.In an earlier study (Elwood et al, 1971) we presented data which showed no evidence of any important difference in certain of the known 'risk factors' such as serum cholesterol and blood pressure, or in two measures of the excitability of the myocardium (QT interval and the presence of extrasystoles). In this paper we present data relating to blood clotting and fibrinolysis.…”
mentioning
confidence: 92%
“…In an earlier study (Elwood et al, 1971) we presented data which showed no evidence of any important difference in certain of the known 'risk factors' such as serum cholesterol and blood pressure, or in two measures of the excitability of the myocardium (QT interval and the presence of extrasystoles). In this paper we present data relating to blood clotting and fibrinolysis.…”
mentioning
confidence: 92%